A novel implant system dedicate to hydraulic Schneiderian membrane elevation and simultaneously bone graft augmentation: An up-to 45 months retrospective clinical study. Issue 8 (August 2016) - Tallarico, Marco; Better, Haddar; De Riu, Giacomo; Meloni, Silvio Mario
Abstract: Purpose: To evaluate clinical and radiographic performance of a novel implant system that allows for hydraulic Schneiderian membrane elevation and simultaneously bone graft augmentation. Materials and methods: Sixty-two consecutive patients with a mean age of 53.1 years and a severe atrophy of the posterior maxilla (3.0 to 7.0 mm) underwent 64 transcrestal sinus floor elevations and submerged implant placement. The following clinical and radiographic parameters were assessed: implant failure, any complications and bone gain measured using cone beam computed tomography. Results: No patient dropped out. No implants failed and all the prostheses were uneventful at the last follow-up examination (mean 23.0 months; range 12–45). All the procedures were completed successfully, with elevation of the sinus membrane and insertion of bone graft and the dental implant at the planned site. No intraoperative or postoperative adverse events were observed, such as membrane tears or facial hematoma. The mean residual alveolar ridge height was 5.2 ± 1 mm (range 3.3–7.0 mm). Mean bone gain was 10.9 ± 2.43 mm (range 5.3–16.5) after an average healing period of 8 months. Conclusions: Hydraulic elevation of the Schneiderian membrane using the iRaise sinus-lift system (Maxillent Ltd) can be considered a valuable treatment option for the rehabilitation of atrophic edentulous posterior maxillae.